Impact of the Commercial Introduction of Transcatheter Mitral Valve Repair on Mitral Surgical Practice. Issue 7 (9th April 2020) - Niikura, Hiroki; Gössl, Mario; Bae, Richard; Sun, Benjamin; Askew, Judah; Harris, Kevin; Mudy, Karol; Strauss, Craig; Stanberry, Larissa; Sweeney, Andrea; Sorajja, Paul
Abstract : Background: There has been uncertainty regarding the effect of transcatheter mitral valve repair (TMVr) with MitraClip on cardiac surgical practice. Our aim was to examine the impact of the commercial introduction of TMVr to a comprehensive mitral program. Methods and Results: We evaluated 875 patients (aged 69±14 years; 58% men) who underwent transcatheter or mitral surgical procedures over a 6‐year period at our institution. Main outcomes were changes in surgical procedural volume after TMVr introduction and short‐term mortality for surgical and TMVr procedures. The numbers of patients treated with MitraClip, isolated mitral repair, and any mitral surgery were 249, 292, and 626 patients, respectively. Compared with surgery, patients with MitraClip were older (aged 82±8 versus 64±12 years; P <0.001) and had more severe morbidity. Following the introduction of MitraClip, surgical volumes steadily increased to a rate of 10 (95% CI, 3–7) procedures per year for isolated mitral procedures and 17 (95% CI, 13–20) procedures per year for all mitral surgeries. Both MitraClip and surgical volumes increased at the same rate ( P =0.42). In‐hospital mortality was 3.2% for MitraClip and 2.1% for all mitral surgeries ( P =0.33). At 30 days, survival free of all mortality ( P =0.17) and freedom from heart failure rehospitalization ( P =0.75) were similar for transcatheter and surgical procedures. Conclusions: The commercial introduction of TMVr may be associated with growth in cardiac surgery, without detracting from other therapies, and favorable clinical outcomes for all treated mitral regurgitation patients. These findings demonstrate the potential benefits of complementary therapies in the treatment of patients with mitral regurgitation.